Bright Light Therapy for MDD in Children and Adolescents: a narrative review of literature - R. Vadukapuram; C. Trivedi; Z. Mansuri; K. Shah; A. Reddy (European Psychiatry, 2022)
Introduction Major Depressive Disorder (MDD) is a common mood disorder diagnosed in children and adolescents. Bright light therapy has been effective for seasonal affective disorders, however its role in the treatment of MDD is under studied.